The 5q- syndrome. - Giagounidis, A; Germing, U; Wainscoat, J; Boultwood, J; Aul, C (2004)
The 5q- syndrome is a distinct hematological disorder with typical laboratory, morphological, cytogenetic, molecular, and prognostic features. It is defined as a myelodysplastic syndrome with a medullary blast count <5% and an isolated interstitial deletion of the long arm of chromosome 5, including bands q31-q33. The molecular basis of this disease has not yet been fully elucidated, but there is evidence that a commonly deleted region of 1.5 Mb harbors one or several tumor suppressor genes, the loss of which being the basic event leading to disease activity. The 5q- deletion has been demonstrated in very early hematopoietic precursors, including CD34+CD133+ and CD34+CD38-Thyl+ cells. Analysing data of 60 patients with the 5q- syndrome that were followed over a period of up to 28 years, we found a median age at diagnosis of 66.8 years and a female preponderance with a male to female ratio of 1:1.5. Anemia is usually macrocytic and combined with low reticulocyte counts and high erythropoetin levels. Three types of cytogenetic deletion are most prevalent: del(5)(q13q33), del(5)(q13q31) and del(5)(q22q33). The 5q- syndrome has a good prognosis with a median overall survival of 107 months at a median follow-up of 53 months, and a low probability of transformation to AML. An increase of the medullary blast count to > or =5% or the addition of one karyotypic anomaly severely reduces median overall survival. The most promising therapeutic approach is the novel thalidomide analogue CC5013 that is currently evaluated in an international phase II study.